Benefits of oral Polypodium Leucotomos extract in MM high‐risk patients. (31st July 2012) - Aguilera, P.; Carrera, C.; Puig‐Butille, J.A.; Badenas, C.; Lecha, M.; González, S.; Malvehy, J.; Puig, S.
Abstract: Background UV radiation and the presence of melanocytic nevi are the main risk factors of sporadic melanoma (MM). Protection of skin by an oral photoprotective agent would have substantial benefits. Objective We investigated the possible role of an oral Polypodium leucotomos (PL) extract to improve systemic photoprotection in patients at risk of skin cancer analyzing the ability to decrease UV‐induced erythema. We also studied the interaction among MC1R polymorphisms and CDKN2A status with the minimal erythematous dose (MED) and their influence in the response after oral PL. Methods A total of 61 patients (25 with familial and/or multiple MM, 20 with sporadic MM and 16 with atypical mole syndrome without history of MM) were exposed to varying doses of artificial UVB radiation without and after oral administration of a total dose of 1080mg of PL. Results Oral PL treatment significantly increased the MED mean in all group patients (0.123 to 0.161 J/cm 2, p<0.05). Although not significant, we noticed a stronger effect of PL on the MED of patients with familial MM compared to those with MM ( U =273, p=0.06). Among the patients with familial MM, those exhibiting a mutated CDKN2A and/or polymorphisms in MC1R had the bigger differences in response to treatment with PL. Limitations Reduced number of patients. No control population. Conclusions Administration of PL leads to a significant reduction of sensitivity to UVR (p<0.05) in all patients. Dark‐eye patients and patients with higher UVR sensibility (lower basal MED) would be the most benefited from oral PL treatment.